2013
DOI: 10.1590/s2236-89062013000400010
|View full text |Cite
|
Sign up to set email alerts
|

Laeliinae (Orchidaceae) do parque nacional do Caparaó, Estados do Espírito Santo e Minas Gerais, Brasil

Abstract: -(Laeliinae (Orchidaceae) from Parque Nacional do Caparaó, Espírito Santo and Minas Gerais States, Brazil). This work aims to identify and characterize species of subtribe Laeliinae (Orchidaceae) occurring in the Parque Nacional do Caparaó, between Minas Gerais and Espírito Santo States. The vegetation in the area comprises forests and campos de altitude, occurring at around 2,000 m, and the highest peak is the Pico da Bandeira, the highest point in the Southeastern region of Brazil with 2,890 m. Laeliinae is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 11 publications
1
5
0
4
Order By: Relevance
“…E. patens). The results of the present study corroborate data presented by Forster and Souza (2007). These authors reported that Encylia patens, Epidendrum armeniacum (widely distributed throughout South America) and E. secundum (throughout the Americas) are well represented in Caparaó.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…E. patens). The results of the present study corroborate data presented by Forster and Souza (2007). These authors reported that Encylia patens, Epidendrum armeniacum (widely distributed throughout South America) and E. secundum (throughout the Americas) are well represented in Caparaó.…”
Section: Discussionsupporting
confidence: 93%
“…The greatest diversity of Laeliinae in Brazil is found in the Atlantic Forest (Flora do Brasil 2020), and new species from this phytogeographic domain have frequently been described (Barberena and Gonzaga 2016). The richness of Laeliinae species in PARNA Itatiaia is higher than in other Brazilian Atlantic Forest remnants where taxonomic studies of the subtribe have been conducted (Barbero 2007, Forster and Souza 2007, Romanini and Barros 2007, Nardy et al 2016). Most of the Laeliinae species (73%) in PARNA Itatiaia are found exclusively in montane vegetation, whereas four species (12%) are restricted to upper montane forest and two species (Epidendrum chlorinum and E. secundum) occur in both phytophisiognomies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A baixa representatividade de coleções para a região do Caparaó é mais expressiva para a vertente capixaba, para a qual há apenas uma listagem florística de plantas vasculares disponível na literatura (Zorzanelli et al 2017). Os demais estudos da vegetação publicados até o presente momento para a região, foram realizados em localidades situadas no estado de Minas Gerais, por exemplo Leoni & Chautems (2004), Mazine & Souza (2008), Forster & Souza (2013) e Moraes et al (2014).…”
unclassified
“…Foster, G. Hatschbach, M. Brugger, L. Krieger, V. C. Souza e L. Leoni (Mota 2012). Em relação aos trabalhos taxonômicos sobre a flora do Caparaó, foram publicados tratamentos para vários grupos como: Violaceae (Souza & Souza 200), Plantaginaceae (Souza & Souza 2002), Ericaceae (Romão & Souza, 2003), Gesneriaceae (Leoni & Chautems 2004), Eriocaulaceae (Trovó et al 2006), Melastomataceae (Faria et al 2006), Myrtaceae (Mazine & Souza 2008), Begoniaceae (Feliciano et al 2010), Laeliinae-Orchidaceae (Forster & Souza 2013) e Bromeliaceae (Mota et al 2016).…”
Section: Não Publicados)]unclassified